A short account of a series of anthropometric observations carried out on girls, 6 - 18 years - Thompson, E.(Elizabeth Jane Clifford) (Stellenbosch : Stellenbosch University, 2012)
Thesis (B. Ed. Ph.) -- University of Stellenbosch, 1944.